2020
DOI: 10.1111/imj.14685
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of H7N9 avian influenza pneumonia: a retrospective analysis of 17 cases

Abstract: Background H7N9 avian influenza is an infection of public health concern, in part because of its high mortality rate and pandemic potential. Aims To describe the clinical features of H7N9 avian influenza and the response to treatment. Methods Clinical, radiological and histopathological data, and treatment‐related of H7N9‐infected patients hospitalised during 2014–2017 were extracted and analysed. Results A total of 17 H7N9 patients (three females; mean age, 58.4 ± 13.7 years) was identified; of these six died… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(39 reference statements)
4
1
0
Order By: Relevance
“…One week after onset of the COVID-19 infection, the clinical condition of the disease can become severe, progressing with hypoxemia and dyspnea, and rapidly develop to acute respiratory distress syndrome (ARDS) in 17% of patients, and 65% of these patients worsened and died due to multi-organ dysfunction 3,4,5 . Similar clinical characteristics have also been observed in patients infected with other highly pathogenic respiratory viruses such as the severe acute respiratory syndrome (SARS) virus (SARS-CoV) 6 , the middle east respiratory syndrome (MERS) virus (MERS-CoV) 7 , and the avian H1N5 and H7N9 influenza viruses 8,9 . In some cases the viral load was low or undetectable at the time of severe illness 10 , suggesting that there were other causes of death than the virus alone.…”
supporting
confidence: 60%
“…One week after onset of the COVID-19 infection, the clinical condition of the disease can become severe, progressing with hypoxemia and dyspnea, and rapidly develop to acute respiratory distress syndrome (ARDS) in 17% of patients, and 65% of these patients worsened and died due to multi-organ dysfunction 3,4,5 . Similar clinical characteristics have also been observed in patients infected with other highly pathogenic respiratory viruses such as the severe acute respiratory syndrome (SARS) virus (SARS-CoV) 6 , the middle east respiratory syndrome (MERS) virus (MERS-CoV) 7 , and the avian H1N5 and H7N9 influenza viruses 8,9 . In some cases the viral load was low or undetectable at the time of severe illness 10 , suggesting that there were other causes of death than the virus alone.…”
supporting
confidence: 60%
“…In this research, we found the higher proportion of male patients in the H7N9 group, which was similar to the data from some previous clinical studies, which can be explained by more involvement of males in poultry breeding and slaughtering [7][8][9]. By comparison, cough and chest tightness were more common in the in uenza groups compared with the COVID-19 group.…”
Section: Discussionsupporting
confidence: 90%
“…One week after onset of the COVID-19 infection, the clinical condition of the disease can become severe, progressing with hypoxemia and dyspnea, and rapidly develop to acute respiratory distress syndrome (ARDS) in 17% of patients, and 65% of these patients worsened and died due to multi-organ dysfunction 3,4,5 . Similar clinical characteristics have also been observed in patients infected with other highly pathogenic respiratory viruses such as the severe acute respiratory syndrome (SARS) virus (SARS-CoV) 6 , the middle east respiratory syndrome (MERS) virus (MERS-CoV) 7 , and the avian H1N5 and H7N9 influenza viruses 8,9 . In some cases the viral load was low or undetectable at the time of severe illness 10 , suggesting that there were other causes of death than the virus alone.…”
supporting
confidence: 60%